Prolonged adaptability of highly qualified athletes to training stresses, studied by longitudinal metabolomic analysis of biofluids - Viryus, E. D.; Dikunets, M. A.; Fedotova, E. V.; Dudko, G. A. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to determine the feasibility of longitudinal metabolome analysis of biological samples from elite athletes to identify previously unknown and highly sensitive metabolic processes associated with long-term adaptation to intense training.